The San Francisco system and its legacies
1 online resource (xviii, 290 pages)
Keywords: "In September 1951, Japan signed a peace treaty with forty-eight countries in San Francisco; in April 1952, the treaty came into effect. The San Francisco Peace Treaty is an international agreement that in significant ways shaped the post-World War II international order in the Asia-Pacific. With its associated security arrangements, it laid the foundation for the regional structure of Cold War confrontation, and the resultant "San Francisco System" fully reflected the strategic interests and policy priorities of the peace conference's host nation, the United States. The treaty fell far short of settling outstanding issues in the wake of the Pacific War or facilitating a clean start for the "post-war" period. Rather, critical aspects of the settlement were left equivocal, and continue to have significant and worrisome implications for regional international relations. This book examines the key developments of the contentious political and security issues in the Asia-Pacific that share a common foundation in the post-war disposition of Japan, particularly the San Francisco Peace Treaty. These include both tangible and intangible issues, such as disputes over territories and "history" problems. Taking the San Francisco System as its conceptual grounding, the authors examine how these issues developed and have remained contentious long after the San Francisco arrangements. To provide bases for producing solutions, the chapters offer comprehensive accounts that explain and deepen our understanding of these complex regional issues and the San Francisco System as a whole"--